2014
DOI: 10.1039/c4ra04144e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of superoleophobic hierarchical surfaces for low-surface-tension liquids

Abstract: This study demonstrates the fabrication of hierarchical surfaces with super -repellency even for low-surface-tension liquids, including octane (surface tension of 21.7 mN m −1 ). Dual-pore surfaces were prepared by a combination of practical wet processes on an alumin ium substrate: chemical etching, anodizing, and organic monolayer coating. Th e size of the larger pores formed by the chemical etching of aluminium is controlled by the concentration of HCl in the CuCl 2 /HCl etching solution. The etched alumini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…The chemical etching with FHH solution led to the creation of pits that, given the crystalline structure of aluminum, are distributed hierarchically in cubic forms forming numerous micro and sub‐micrometric plateaus, interconnected and evenly distributed over the whole surface of the substrate. In agreement with previous works, this kind of microstructure is typical of aluminum surfaces obtained in processes involving etching with HCl …”
Section: Resultssupporting
confidence: 92%
“…The chemical etching with FHH solution led to the creation of pits that, given the crystalline structure of aluminum, are distributed hierarchically in cubic forms forming numerous micro and sub‐micrometric plateaus, interconnected and evenly distributed over the whole surface of the substrate. In agreement with previous works, this kind of microstructure is typical of aluminum surfaces obtained in processes involving etching with HCl …”
Section: Resultssupporting
confidence: 92%
“…The authors recently reported that micro‐/nanodual pore aluminum surfaces produced by chemical etching and anodizing of high purity aluminum show superoleophobicity even for low‐surface‐tension liquids, such as octane, after fluoroalkylphosphonic acid coating . Figure shows scanning electron microscope (SEM) images of the surfaces in this study, where we utilized this hierarchical surface with cylindrical nanopores to add a healing agent into the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Low magnification SEM images reveal microscale roughness developed by chemical etching. The chemical etching of aluminum in a mixed solution of HCl + CuCl 2 forms a number of crystallographic etch pits with a half‐cubic morphology as the basic structural unit of each pit . The dissolution of aluminum occurs preferentially in the crystallographic 〈100〉 direction, and the size of pits is controlled by the rate of saturation precipitation of AlCl 3 that induces passivation of the pits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before nanoimprinting, phosphonic acid-based SAM (TDPA) was coated on the nanostructured aluminum surface (Fig. 8a) [52][53]. In this procedure, the nanostructured aluminum specimen was immersed in a TDPA ethanol solution for 2 days.…”
Section: Polymer Nanoimprinting Using Nanostructured Aluminum Moldsmentioning
confidence: 99%